2018
DOI: 10.1158/1538-7445.am2018-2620
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 2620: Aquaporin 11 as a new predictive biomarker of overall survival and platinum-based chemotherapy response in lung adenocarcinoma patients

Abstract: Background: Biomarkers predictive of response to chemotherapy are critically needed for the precise selection of treatment protocols in lung adenocarcinoma (LUAD). Aquaporins (AQPs), transmembrane water channels, are emerging targets in cancer. Recently discovered, non-ubiquitous family member aquaporin 11 (AQP11), a tissue-specific endoplasmic reticulum (ER) resident, was identified as a cellular pro-survival factor implicated in the maintenance of ER homeostasis. AQP11 is mapped to 11q13-q14 amplicon harbori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Clinical trials indicated high expression of AQP8 was associated with better prognoses and overall survival in colon cancer [ 92 ]. AQP11 transcripts, at high levels, have been associated with poor survival in lung adenocarcinoma [ 93 ] but, conversely, better survival in breast cancer [ 94 ], suggesting cancer-specific contributions of different classes of aquaporins. Selective inhibitors for AQPs 8 and 11 remain to be identified; in the interim, interfering RNA knockdown techniques might be used to explore the possible roles of these channels in EC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials indicated high expression of AQP8 was associated with better prognoses and overall survival in colon cancer [ 92 ]. AQP11 transcripts, at high levels, have been associated with poor survival in lung adenocarcinoma [ 93 ] but, conversely, better survival in breast cancer [ 94 ], suggesting cancer-specific contributions of different classes of aquaporins. Selective inhibitors for AQPs 8 and 11 remain to be identified; in the interim, interfering RNA knockdown techniques might be used to explore the possible roles of these channels in EC cells.…”
Section: Discussionmentioning
confidence: 99%
“…A follow-on study using matched mRNA expression, survival, and drug response data from TCGA lung adenocarcinoma dataset (N = 369), In this report, Sharpnack et al. have demonstrated that high AQP11 mRNA expression is negatively prognostic in patients with adenocarcinoma of lung (LUAD) ( 199 ). Furthermore, patients with high tumor AQP11 mRNA expression (10.3%) had significantly worse overall survival compared with patients with low AQP11 expression.…”
Section: Role Of Aqps In Human Carcinogenesismentioning
confidence: 90%
“…AQP4 has been implicated in glioma cell migration and their resistance to chemotherapy (Lan et al, 2017). Similarly (Dong et al, 2016), AQP11 is partly responsible for the variations in lung cancer response to chemotherapy (Sharpnack et al, 2018 | 6121 PI3K/AKT, EGF, and some other proliferative signaling pathways.…”
Section: Cancer and Aqp1 Aqp3 Aqp4 Aqp5 And Aqp11mentioning
confidence: 99%